INFLUENCE OF GROWTH REGULATORS UPON CROP PRODUCTIVITY IN DIFFERENT ZONES OF RUSSIA - V. V. Vakulenko (Зерновое хозяйство России, 2018)
In the article the problems of increase of drought and heat tolerance have been considered. The problems connected with application of plant growth regulators to increase productivity, quality of product and crop resistance to abiotic stresses have been considered. The article shows the mechanisms and efficiency of application of growth regulator ‘Zirkon’ (natural mixture of hydroxycinnamic acids and their derivatives extracted from Echinacea purpurea), ‘Epin-Extra’ (analogue of the natural phytohormone epibrassinolide) and silicon-containing chelate micronutrient ‘Siliplant’ for spring and winter wheat and maize under stress. It has been shown that when ‘Epin-Extra’ and ‘Zirkon’ are applied for spring and winter wheat seed preparation and spraying them in the tillering stage, they increase germination, number of productive stems, number of grains in the ear, their mass and productivity in the conditions of moisture shortage and high temperatures. If maize is twice sprayed with these growth regulators in the conditions of extremely high temperatures, the number of cobs per plant, grains per cob and mass of 1000 grains will increase.  Fertilizing of ‘Siliplant’ in the tillering stage enhances drought and heat tolerance of grain crops, promotes productive stalk density and improves the main features of the harvest, i.e. ear length, number and mass of grains in the ear.